Does adding a psychosocial cessation intervention to an existing life-skills and tobacco-prevention program influence the use of tobacco and supari among secondary school students?: Findings from a quasi-experimental trial in Mumbai, India - Chatterjee, Nilesh (Tob Prev Cessat, 2019)
INTRODUCTION: This study aimed to test whether school-going adolescents who self-report tobacco and/or supari use are more likely to quit if a school-based psychosocial cessation intervention is added to an existing life-skills and tobacco-prevention program. METHODS: A quasi-experimental trial with pre-test and post-test 20 weeks after the intervention was conducted with students from low-income families in 12 schools in Mumbai; six schools were randomly assigned to the intervention and the remaining to the comparison condition. Participants were students from grades 7, 8 and 9 who self-reported tobacco and/or supari use. Intervention schools received six sessions of LifeFirst, a psychosocial group-based tobacco cessation intervention program, in addition to SuperArmy, a school-wide life-skills and tobacco-prevention program. Trained counselors facilitated the cessation intervention, which spanned five months. All students in comparison schools received only SuperArmy. The outcome measures were self-reported use of tobacco-only, supari-only, and tobacco plus supari in the past 30 days. RESULTS: The number of all users decreased by 19.1% in the intervention and 18.7% in the comparison schools at post-test. Although this reduction was significant (p<0.001) within each group, the difference between intervention and comparison schools was not significant. Further segregation by type of product used showed that for tobacco-only users there was a non-significant increase of 1.7% in intervention schools, and a significant 26.2% increase (p<0.001) in the comparison group. Tobacco plus supari use declined in both groups; however, supari-only use fell by 14.8% in the intervention and 32.7% in the comparison schools (p<0.01). CONCLUSIONS: The combination of a cessation intervention along with the life-skills and tobacco-prevention program appear to have halted tobacco-only use in the intervention group. Future research needs to determine whether students are substituting supari for tobacco and to understand the psychological mechanisms underlying the cessation intervention and the interaction between cessation and prevention-only interventions.